DEVELOPMENT OF A FUNCTIONAL BEVERAGE FORMULATION BASED ON BUTTERFLY PEA EXTRACT AND EVALUATION OF ITS ORGANOLEPTIC AND PHYSICOCHEMICAL PARAMETERS - S.N.Obloberdiyev; G.Sh.Korabekova; F.Sh.G‘ulomova; M.J.Bekmurodova; Sh.E.Ulashova; Z.A.Madusmonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. this study focuses on the development of a functional beverage formulation based on butterfly pea (clitoria ternatea l.) extract and the evaluation of its organoleptic and physicochemical parameters. the beverage was prepared using butterfly pea extract, drinking water, sugar, citric acid, and ascorbic acid. the obtained product was assessed by taste, aroma, color, appearance, ph, titratable acidity, and color stability. the results showed that butterfly pea extract can be used as a natural colorant and functional ingredient in beverage production. the developed beverage had an attractive color, pleasant taste, acceptable acidity, and good sensory properties.